Step
*
1
of Lemma
rnonzero-lemma1
1. x : ℕ+ ⟶ ℤ
2. n : ℕ+
3. 5 ≤ |x n|
4. m : ℕ+
5. n ≤ m
6. |(m * (x n)) - n * (x m)| ≤ ((2 * 1) * (n + m))
7. |m * (x n)| ≤ ((2 * m) + (2 * n) + |n * (x m)|)
⊢ m ≤ (n * |x m|)
BY
{ ((RWO "absval_mul" (-1) THENA Auto) THEN (RWO "3<" (-1) THENA Auto)) }
1
1. x : ℕ+ ⟶ ℤ
2. n : ℕ+
3. 5 ≤ |x n|
4. m : ℕ+
5. n ≤ m
6. |(m * (x n)) - n * (x m)| ≤ ((2 * 1) * (n + m))
7. (|m| * 5) ≤ ((2 * m) + (2 * n) + (|n| * |x m|))
⊢ m ≤ (n * |x m|)
Latex:
Latex:
1.  x  :  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
2.  n  :  \mBbbN{}\msupplus{}
3.  5  \mleq{}  |x  n|
4.  m  :  \mBbbN{}\msupplus{}
5.  n  \mleq{}  m
6.  |(m  *  (x  n))  -  n  *  (x  m)|  \mleq{}  ((2  *  1)  *  (n  +  m))
7.  |m  *  (x  n)|  \mleq{}  ((2  *  m)  +  (2  *  n)  +  |n  *  (x  m)|)
\mvdash{}  m  \mleq{}  (n  *  |x  m|)
By
Latex:
((RWO  "absval\_mul"  (-1)  THENA  Auto)  THEN  (RWO  "3<"  (-1)  THENA  Auto))
Home
Index